What remains [videorecording (DVD)] - Huang, Ran; Skarsgard, Megan Everett; Skarsgård, Gustaf; Riseborough, Andrea, 1981-; Skarsgård, Stellan (Vantage Media, 2025)
In a psychiatric hospital, a serial killer, his therapist, and a police detective, all have a vested interest in solving a cold case before their obsessive quest consumes them all.